Physicalism - Stoljar, Daniel (London ; New York : Routledge, 2010)
Physicalism, the theory that everything is physical is one of the most controversial ideas in philosophy. In this introduction, the author focuses on three fundamental questions: the interpretation, truth, and philosophical significance of physicalism, while covering the following key topics: history, definitions, challenge from empirical sciences, relationship with physics, relationship with causality, and key debates in metaphysics and philosophy of mind, such as supervenience, identity, and conceivability.
The standard picture -- Form and alternatives -- The starting point view -- The theory view -- Hempel's dilemma -- The necessity view -- Is necessitation necessary? -- Is necessitation sufficient? -- Skeptics and true believers -- Arguments against physicalism -- Arguments for physicalism.
Includes chapter summaries.
Includes bibliographical references (p. [237]-246) and index.
Keywords: Materialism